Anti-RNA polymerase III antibody-associated scleroderma renal crisis in a patient with limited cutaneous systemic sclerosis: A case report. Issue 2 (4th March 2018) - Takada, Daisuke; Hoshino, Junichi; Kikuchi, Koichi; Yabuuchi, Junko; Kogure, Yuta; Ueno, Toshiharu; Sekine, Akinari; Yamanouchi, Masayuki; Sumida, Keiichi; Mise, Koki; Suwabe, Tatsuya; Hayami, Noriko; et al.
Abstract: A 69-year-old Japanese man was presented with hypertensive crisis. Renal histology revealed malignant nephrosclerosis, including an onion skin pattern with fibrinoid necrosis of the small arteries from arterioles up to interlobular arteries. Immunological investigation clarified positive anti-RNA polymerase (RNAP) III antibody, and limited cutaneous systemic sclerosis (Lc SSc) was diagnosed by skin biopsy as the underlying disease causing scleroderma renal crisis (SRC). Angiotensin covering enzyme (ACE) inhibitor therapy and calcium antagonist were effective for his renal condition. Although an association between SRC and anti-RNAP III antibody has already been reported in patients with diffuse cutaneous SSc (Dc SSc), this case indicates that SRC with hypetensive emergency with malignant nephrosclerosis can also be diagnosed on patients with Lc SSc patients by the examination of anti-RNAP III antibody.